2007
DOI: 10.1002/glia.20558
|View full text |Cite
|
Sign up to set email alerts
|

Translocator protein (18 kDa) is involved in the regulation of reactive gliosis

Abstract: Translocator protein (18 kDa) (TSPO), previously known as peripheral‐type benzodiazepine receptor, is a critical component of the mitochondrial permeability transition pore. Brain inflammation results in the induction of the expression of TSPO in glial cells and some TSPO ligands decrease reactive gliosis after brain injury. However, since some TSPO ligands are neuroprotective, their effects on reactive gliosis may be the consequence of a reduced neurodegeneration. To assess whether TSPO ligands can modulate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 77 publications
0
47
0
Order By: Relevance
“…After ischemic insult, activated astrocytes release high levels of nitric oxide, peroxynitrite, glutamate, TNF-α, and IL-1β [38,39]. Although there are some studies on astrocytes in the brain with LPS preconditioning [40][41][42], our finding indicates that the reduction of activated astrocytes may participate in a protective role of LPS preconditioning against ischemic damage.…”
Section: Layers Groupsmentioning
confidence: 44%
“…After ischemic insult, activated astrocytes release high levels of nitric oxide, peroxynitrite, glutamate, TNF-α, and IL-1β [38,39]. Although there are some studies on astrocytes in the brain with LPS preconditioning [40][41][42], our finding indicates that the reduction of activated astrocytes may participate in a protective role of LPS preconditioning against ischemic damage.…”
Section: Layers Groupsmentioning
confidence: 44%
“…By stereotaxic injection of LPS into the substantia nigra (SN) of mouse brains, Bae et al [44] have investigated the antiinflammatory effects of PK11195 and Ro5-4864 in CNS; the reduction in the expression of ionized calcium binding adaptor molecule 1 (Iba-1) and NF-kB and inhibition of the release of iNOS, TNF-α and IL-6 have been evidenced in microglia of SN [44]. Similarly, the LPS infusion in the hippocampus of male rats has suggested that in vivo PK11195 administration has been able to reduce the number of major histocompatibility complex (MHC)-II immunoreactive cells and microglia proliferation; in contrast, Ro5-4864 does not significantly affect the response of microglia to LPS [47].…”
Section: Tspo Ligands In the Treatment Of Neuro-inflammationmentioning
confidence: 94%
“…163 In fact, we have shown in an alpha-synuclein model of 164 PD both in rodents and primates, that the microglia 165 response is early, preceding cell death, but not static 166 (Sanchez-Guajardo et al, 2010;Barkholt et al, 2012). 167 Also in vitro microglia's response to alpha-synuclein is 168 complex, with both pro and anti-inflammatory profiles 169 co-existing in parallel (Reynolds et al, 2008b to apoptosis (Veenman and Gavish, 2012), increased pro-188 liferation and phagocytosis (Choi et al, 2011) and its 189 modulation seems to be indeed involved in microglia acti-190 vation (Veiga et al, 2007). In addition, the limitation to (Gao et al, 2008).…”
mentioning
confidence: 95%